THE EFFECT OF LAVENDER OIL CONCENTRATION ON PREFERENCE AND SKIN IRRITATION OF NIGHT BODY LOTION CONTAINING NANOSTRUCTURED LIPID CARRIERS-UBIQUINONE - Mayangsari, Fransisca Dita; Sakti, Aditya Sindu; Khotimah, Khusnul (Universitas Muhammadiyah Ahmad Dahlan Cirebon, 2025)
Lavender Oil (LO) has a calming scent and antioxidant activity. Therefore, this oil has potential as a fragrance and second active ingredient in Night Body Lotion (NBL) that contained Coenzyme Q10 (CoQ10) loaded Nanostructured Lipid Carrier (NLC) systems. This study aims to observe the effect of LO’s concentration on the physical characteristics, consumer preference level, and skin irritation of NBL that contained NLC-CoQ10. There are three formulas observed in this study, namely F0 (0% LO), F1 (2% LO), and F2 (4% LO). The physical characteristics assessed included organoleptic, homogeneity, pH, spreadability, and viscosity. In vivo skin irritation tests observe erythema and edema on the skin of a white rat. In a consumer preference test, the panelists assess the organoleptic properties of F0, F1, and F3 using a 7-point hedonic scale. Based on the physical characteristic test, it is known that the three formulas have the same color, consistency, homogeneity, and spreadability value. The difference between the three formulas lies in their aroma. F0 is unscented; F1 and F2 have a lavender scent. All formulas have a pH in the range of 5.89-6.06. Statistically, increasing the concentration of LO decreases the pH of NBL. The three formulas have a viscosity in the range of 2.140–2.890 cP. Statistically, the viscosity of NBL increased with the increase in LO concentration. Based on the skin irritation test, it is known that all formulas are non-irritating. Based on preference level analysis, the most preferred formulas based on their scent are F1 and F2.